A pilot study of spiral-wound air gap membrane distillation process and its energy efficiency analysis. (January 2020) - Lee, Chang-Kyu; Park, Chansoo; Woo, Yun Chul; Choi, June-Seok; Kim, Jong-Oh
Abstract: Brine disposal is a major drawback for seawater desalination. Membrane distillation (MD) is an emerging technology to treat a high saline water including brine disposal instead of reverse osmosis, multi-stage flash and multi-effect distillation. This study investigated a pilot scale of a spiral-wound air gap MD (AGMD) module and evaluated its efficiency. A pilot-scale AGMD module with design production capacity of 10 m 3 /d was operated. Experiments with varying flow velocity showed increasing trend of water vapor flux as flow velocity increases. The temperature is one of the significant points in maximizing water permeate vapor flux in MD. Increasing temperature from 65 °C to 75 °C in evaporator channel has increased flux from 0.59 to 1.15 L/m 2 /h. Under various conditions, specific thermal energy consumption (STEC) and gained output ratio (GOR) was used to analyze energy efficiency. The pilot plant showed high GOR value in spite of a limited heating and cooling source available at the site. The highest GOR achieved was 3.54 with STEC of 182.78 kWh/m 3 . This study provides an overview of operation experience and its data analysis related to temperature, concentration, flow rate and energy supply. Graphical abstract: Image 1 Highlights: Pilot study of AGMD plant had its maximum production of 10 m 3 /d. Detailed evaluation of energy efficiency was conducted through STEC and GOR. Increase of evaporator channel temperature caused flux increase. Increasing trend of flux was observed at higher flow velocity. High GOR achieved regardless of a limited heating/cooling source.